A new species of Naxia Latreille, 1825 (Brachyura: Majidae) from deep water off Brazil - Tavares, Marcos; Poore, Gary C. B. (Zootaxa, 2014)
A new species of spider crab, Naxia atlantica n. sp., is described and illustrated from deep waters off São Paulo (southeastern Brazil). The new species can be separated from its congeners by a suite of characters including shapes of the propodi of the walking legs, rostrum and basal antennal article. This is the first record of the genus outside southern Australia and New Zealand.